Patterns of international organizations' engagement in reform and policy making in the post-Soviet space - Anna A. Dekalchuk; Ivan S. Grigoriev; Andrey Starodubtsev (East European Politics, 2024)
The paper explains how states and international organisations interact in policy making by focusing on five countries of the post-Soviet space. Based on in-depth interviews conducted in Armenia, Belarus, Georgia, Kazakhstan, and Uzbekistan, we explore different patterns of state-IO interactions and explain the determinants of these patterns' formation. We demonstrate that these patterns arise from a combination of two country-level factors: political openness of the system and national regulation of international actors' involvement into the policy process. However, the patterns of state-IOs relations prove strongly mitigated by the intervening variable of the national reform ecosystem's configuration and resource endowment.
Keywords: 320; International organisations; reforms; policy process; reform ecosystem; post-Soviet space